The paperless partograph: can it be effective to replace the WHO modified partograph - Deka, Gitanjali; Sharma, Rajashree; Das, Gokul Chandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The partograph is a graphical representation of the various events of labour plotted against time. The main aim was to determine whether the paperless partograph can replace the WHO partograph to monitor labour and aid in decision making. Methods: It is a hospital based prospective analytical study. The course of labour in 400 women with term singleton uncomplicated pregnancies were studied by using either partographs. 12 resident doctors were included to assess the user friendliness and asked to fill 240 separate partographs (120 each of WHO Modified and Paperless partograph). Results: The maternal and perinatal outcome was comparable between both the partographs. The Paperless partograph was however more user-friendly than the WHO partograph (p<0.0001). Conclusions: The Paperless partograph was found to be as effective as the WHO partograph in the effective management of labour. It is more user-friendly and has promising prospects to replace the WHO partograph.